Association of Cortical Hyperexcitability and Cognitive Impairment in Patients With Amyotrophic Lateral Sclerosis. (20th April 2021) - Higashihara, Mana; Pavey, Nathan; van den Bos, Mehdi; Menon, Parvathi; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objective: To determine whether cortical hyperexcitability was more prominent in cognitively impaired patients with amyotrophic lateral sclerosis (ALS). Methods: Threshold tracking transcranial magnetic stimulation (TMS) was used to assess cortical excitability and cognitive function was determined by the Edinburgh Cognitive and Behavioural ALS Screen (ECAS). Cognitive impairment was defined by ECAS < 105. Patients with ALS, defined by the Awaji criteria, were prospectively recruited. Patients unable to undergo TMS, or in whom TMS indices were compromised by coexistent medical conditions, were excluded. Cortical hyperexcitability was defined by reduced short interval intracortical inhibition (SICI) and increased short interval intracortical facilitation (SICF), index of excitability (IE), and motor evoked potential (MEP) amplitude. Student t test determined differences between groups and multivariable regression modeling was used to assess association among cognitive, clinical, and TMS measures. TMS results were compared with those of 42 controls. Results: Cognitive impairment was evident in 36% of the 40 patients with ALS (23 male, mean age 62.1 years). Cortical hyperexcitability was more prominent in cognitively impaired patients as indicated by an increase in SICF (ECAS≥105 –15.3 ± 1.7%, ECAS<105 –20.6 ± 1.2%; p < 0.01), IE (ECAS ≥105 80.9 ± 7.8, ECAS <105 95.0 ± 4.5; p < 0.01), and MEP amplitude (ECAS≥105 28.7 ± 3.3%, ECAS<105 43.1 ± 5.9%; p < 0.05). SICF was independently associated with the ECAS score ( β = 2.410; p < 0.05). Reduced SICI was evident in ALS, being more prominent in patients with reduced executive score (ECASexecutive score>33 6.2 ± 1.3%, ECASexecutive score<33 1.5 ± 2.1%; p < 0.01). Conclusion: Cortical hyperexcitability was more prominent in cognitively impaired patients with ALS than in controls. Given that ECAS is a valid predictor of TDP-43 pathology, the increase in cortical hyperexcitability may be associated with TDP-43 accumulation.